2008
DOI: 10.1111/j.1365-2850.2008.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between community violence exposure and mental health symptoms in urban adolescents

Abstract: Urban adolescents are exposed to a substantial amount of community violence which has the potential to influence psychological functioning. To examine the relationship between community violence exposure and mental health symptoms in urban adolescents, a literature review using MEDLINE, CINAHL, PubMed, PsycINFO, CSA Social Services, and CSA Sociological Abstracts was conducted. Search terms included adolescent/adolescence, violence, urban, mental health, well-being, emotional distress, depression, anxiety, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
99
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 47 publications
13
99
0
2
Order By: Relevance
“…Some have suggested that desensitization to violence occurs (McDonald & Richmond, 2008). For example, it has been found that some adolescents adapt to violence, which would explain a lack of/or decrease in incidents of psychological distress (McDonald & Richmond, 2008).…”
Section: The Impact Of Violencementioning
confidence: 98%
“…Some have suggested that desensitization to violence occurs (McDonald & Richmond, 2008). For example, it has been found that some adolescents adapt to violence, which would explain a lack of/or decrease in incidents of psychological distress (McDonald & Richmond, 2008).…”
Section: The Impact Of Violencementioning
confidence: 98%
“…PTSD has been established as a common mental health outcome associated with exposure to violence (McDonald and Richmond 2008;Schwab-Stone et al 1999;Singer et al 1995), as well as a predictor of violence perpetration (Fehon et al 2005;Flannery et al 2001;Jakupcak and Tull 2005;Lee andHoaken 2007, Moretti et al 2006). In their review of twenty-six studies, McDonald and Richmond (2008) concluded that PTSD and aggression were outcomes most strongly related to exposure to community violence. Fehon et al (2005) and Flannery Singer, and Wester (2001) both found that youth who reported engaging in violent behaviors had higher levels of both exposure to violence and symptoms of PTSD than nonviolent youth.…”
Section: Introductionmentioning
confidence: 98%
“…2005; Fowler, Tompsett, Braciszewski, Jacques-Tiura, & Baltes, 2009;McDonald & Richmond, 2008;Trickett, Duran, & Horn, 2003). In 2000, Guterman and colleagues specifically recommended that researchers in this area include clear conceptual and operational definitions of community violence to allow comparisons across studies.…”
mentioning
confidence: 98%